Analysis of Body Shaming Construction on Women in the Film "Imperfectâ€ - Mustafa, Moch. Turdi; Sukarno, Sukarno; Setiawan, Ikwan (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
The portrayal of body shaming against women in films is a social critique of the act of body shaming. Hence, the study of body shaming in films is intriguing for future investigation. The objective of this research is to uncover the portrayal of body shaming towards women in films. The research data comprised of words and phrases that encompassed body shaming and were examined utilizing Norman Fairclough's Critical Discourse Analysis approach. The data was acquired from the movie Imperfect: Karir, Cinta & Timbangan. This study is also classified as critical-qualitative research. The research findings indicate that the film â€œImperfect: Karir, Cinta & Timbanganâ€ portrays three types of body shaming, which include comparing, commenting, and insulating individuals based on their physical appearance. Furthermore, the film's production background is influenced by the film development genre in Indonesia, and the producer's background as a comedian aligns with the genre of the film. In addition, this also highlights that the film production is also considered to have some motives to depict body shaming in the film, including the commercial motive, social culture, and ideology to struggle.